Igor Orestovich Kulik To the 75th birthday anniversary - Omelyanchouk, A.N.; Shekhter, R.I. (Физика низких температур, 2010)
Igor Orestovich Kulik — a prominent physicist and an outstanding representative of Kharkov’s school of theoretical physics, Corresponding member of the National Academy of Sciences of Ukraine and Ukrainian State Prize Laureate — will be 75 on November 19 this year.